The Prevalence of Intestinal Parasitic Infections in Ahvaz, Southwest of Iran, during 2007–2017 - ALASVAND JAVADI, Roya (Iran J Public Health, 2019)
BACKGROUND: Intestinal parasitic infections (IPIs) are frequently considered one of the public health problems worldwide. Therefore, we aimed to evaluate the prevalence of IPIs among patients. METHODS: In this Retrospective cross-sectional study, 50000 stool samples (24551 males) were collected among males and females referred to Naft Hospital of Ahvaz, southern Iran during 2007–2017. At first, the collected specimens were macroscopically observed for the presence of trophozoites, eggs, cysts using the procedure of direct as well as the method of formalin-ether concentration. RESULTS: Of 50000 samples, 2878 (5.75%) cases were positive for IPIs that 1426 and 1452 cases were observed in the males and females, respectively. Giardia lamblia with 887 (1.774%) cases, Blastocystis hominis with 784 (1.568%) cases, Entamoeba histolytica/dispar with 685 (1.37%) cases, E. coli with 357 (0.714%) cases, Trichomonas hominis with 43 (0.086%) cases, Chilomastix mesnili with 40 (0.08%) cases, Hymenolepis nana with 38 (0.076%) cases, Lodamoeba butschlii with 25 (0.05%) cases, Endolimax nana with 18 (0.036%) cases, Taenia saginata proglottid with one (0.002%) case were found. CONCLUSION: Our finding showed a relatively high prevalence of IPIs among people referred to Naft Hospital of Ahvaz, southern Iran during 2007–2017.